Fish can smell trace metals at environmentally relevant concentrations in freshwater. (July 2018) - Lari, Ebrahim; Bogart, Sarah J.; Pyle, Greg G.
Abstract: The objective of the present study was to investigate the ability of the olfactory system of rainbow trout ( Oncorhynchus mykiss ) to detect three trace metals, cadmium (Cd), copper (Cu), and nickel (Ni), using electro-olfactography (EOG). The olfactory response to all three metals was measured at either 10 −6 M or at a concentration established by Alberta Environment and Parks (AEP) as the criterion for the protection of aquatic life. Results of the present study demonstrated that the olfactory system of rainbow trout can detect all three metals (i.e. Cd, Cu, and Ni) in water at environmentally relevant concentrations. These results provide physiological evidence for a role of the olfactory system in fish behavioural responses (as shown in previous studies) when they encounter metal contaminated waters. Highlights: Rainbow trout can detect nickel at environmentally relevant concentrations. Rainbow trout can detect copper at environmentally relevant concentrations. Rainbow trout can detect cadmium at environmentally relevant concentrations.